AKIBAT HUKUM PENANGKAPAN IKAN DENGAN TIDAK MEMILIKI SURAT IZIN PENANGKAPAN IKAN (STUDI PUTUSAN NOMOR 2/PID.SUS-PRKN/2019/PN.MME): Legal Consequences Of Fishing Without A Fishing License (Decision Number 2/Pid.Sus-Prkn/2019/PN.Mme) - Fania Nur Halimah; Endang Pandamdari (Faculty of Law, Universitas Trisakti, 2024)
A fishing license is a written permitthat every fishing vessel must have to conduct fishing. The formulation of the problem in this study is how fishing by Gani who does not have a fishing license (SIPI) is reviewed from the Fisheries law, and what are the legal consequences of fishing by Gani without a Fishing License (SIPI) based on the Study of decision Number 2/Pid.Sus-Prkn/Pn.Mme. This research uses descriptive normative legal research methods, the type of data uses secondary data and is studied qualitatively, so that way of drawing conclusions uses deductive logic. This research leads to regulations on the supervision and control of fishing activities that damage fisheries resources, which in this case are regulated in west Nusa Tenggara Province Regional Regulation Number 8 of 2020. The result of the study explain that Gani in conducting fishing has violated the provisions of the Fisheries Law, violating the licensing requirements and the use of fishing gear, namely compressors, which caused gani as a ship owner to be found guilty of committing a fishing crime, namely violating Article 27 paragraph 1 of the Fisheries Law, because a Fishing License must be owned when fishing.